Optical Sensor Based on Surface Plasmon Resonance Measurements - W. Mahmood Mat Yunus; Rosmiza Mokhtar; Mohd Maarof Moksin; Chong Boon Peng; Lee Woei Yeh (Universitas Gadjah Mada, 2000)
Optical Sensor Based on Surface Plasmon Resonance Measurements